Refractive index sensor based on an abrupt biconical fiber taper - He, Yan. (2013)
In this project, a novel refractive index (RI) sensor based on the abruptly tapered biconical fiber was proposed and demonstrated. The RI sensor is based on the theory of mode coupling in the tapered fiber. It has been shown that when a single mode fiber is tapered, the fundamental mode will be coupled into cladding mode and core mode in the tapered region. The transmission power spectrum of the tapered fiber has sinusoidal relation with the wavelength. The change of the external RI of the solution can be reflected in the shift of the wavelength response.